2010
DOI: 10.2337/db09-1105
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Adipose Glutathione S-Transferase A4 Leads to Increased Protein Carbonylation, Oxidative Stress, and Mitochondrial Dysfunction

Abstract: OBJECTIVEPeripheral insulin resistance is linked to an increase in reactive oxygen species (ROS), leading in part to the production of reactive lipid aldehydes that modify the side chains of protein amino acids in a reaction termed protein carbonylation. The primary enzymatic method for lipid aldehyde detoxification is via glutathione S-transferase A4 (GSTA4) dependent glutathionylation. The objective of this study was to evaluate the expression of GSTA4 and the role(s) of protein carbonylation in adipocyte fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
191
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 49 publications
14
191
0
2
Order By: Relevance
“…GSTA4 is a cytoplasmic enzyme that translocates to the mitochondrion under conditions of oxidative stress (26). Previous results have demonstrated that selective loss of GSTA4 protein results in increased total protein carbonylation and mitochondrial dysfunction, yet the mitochondrial targets of such modification have not been identified (11). To address the role of protein carbonylation in adipocyte mitochondrial dysfunction, we utilized a strategy based on loss or gain-of-function of GSTA4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…GSTA4 is a cytoplasmic enzyme that translocates to the mitochondrion under conditions of oxidative stress (26). Previous results have demonstrated that selective loss of GSTA4 protein results in increased total protein carbonylation and mitochondrial dysfunction, yet the mitochondrial targets of such modification have not been identified (11). To address the role of protein carbonylation in adipocyte mitochondrial dysfunction, we utilized a strategy based on loss or gain-of-function of GSTA4.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of GSTA4 in cultured 3T3-L1 adipocytes or in adipose tissue from high fat-fed C57Bl/6J mice leads to elevated mitochondrial carbonylation, diminished respiration, and altered metabolic flux through the tricarboxylic acid cycle and ␤-oxidation pathways (11). In addition, obesity-induced insulin resistance in humans positively correlates with protein carbonylation, indicating that increased oxidative stress leads to increased levels of carbonylated proteins (27).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations